Analisis Daya Dukung dan Daya Tampung Lahan Pembangunan Fisik Berkelanjutan Di Distrik Mayamuk dan Distrik Salawati - Agung Rizky Prasetiyo; Slamet Widodo; Anif Farida; Nurbia Nurbia (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2025)
This study aims to determine the land carrying capacity for sustainable physical development in Mayamuk District and Salawati District and to determine the land carrying capacity for sustainable physical development in Mayamuk District and Salawati District. The methods used in the study include spatial analysis and quantitative descriptive analysis. The results of the study obtained the carrying capacity of residential land in Mayamuk District and Salawati District with a free class of 6,497.99 ha, a somewhat free class of 35,686.57 ha, and a non-free class of 1,873.18 ha. The area of land that can be developed as a residential area is available at 6,874.45 ha from the total area of Mayamuk District and Salawati District, which is 44,057.74 ha. The land carrying capacity of Mayamuk and Salawati Districts is 6,874.45 hectares, with 4,812.12 hectares of potential land available for housing, capable of accommodating approximately 473,414 housing units and 1,893,656 residents. Therefore, Mayamuk and Salawati Districts are still able to accommodate population growth in 2033